2017
DOI: 10.1186/s12881-017-0425-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 31-year-old patient with SYNGAP1 gene defect points to importance of variants in broader splice regions and reveals developmental trajectory of SYNGAP1-associated phenotype: case report

Abstract: BackgroundWhole exome sequencing is a powerful tool for the analysis of genetically heterogeneous conditions. The prioritization of variants identified often focuses on nonsense, frameshift and canonical splice site mutations, and highly deleterious missense variants, although other defects can also play a role. The definition of the phenotype range and course of rare genetic conditions requires long-term clinical follow-up of patients.Case presentationWe report an adult female patient with severe intellectual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
2
22
1
2
Order By: Relevance
“…De novo SYNGAP1 mutations have been found in patients with ID, epilepsy, or ASD [11][12][13][14][15][16][17][18][19][20] . In a large-scale developmental disorders study, seven SYNGAP1 mutations were identified in 940 patients with ID; therefore, the frequency of SYNGAP1 mutations is suggested to be ∼0.74% in patients with ID 19 .…”
Section: Introductionmentioning
confidence: 99%
“…De novo SYNGAP1 mutations have been found in patients with ID, epilepsy, or ASD [11][12][13][14][15][16][17][18][19][20] . In a large-scale developmental disorders study, seven SYNGAP1 mutations were identified in 940 patients with ID; therefore, the frequency of SYNGAP1 mutations is suggested to be ∼0.74% in patients with ID 19 .…”
Section: Introductionmentioning
confidence: 99%
“…encephalopathies have a slow developmental regression that is primarily due to seizures, interictal spikes (IISs), or cortical dysrhythmia identified on EEG (19,20). Case reports indicate that adult patients demonstrate gradual decline in cognitive abilities (21). Perampanel (PMP), an AMPA receptor (AMPAR) antagonist recently approved by the Food and Drug Administration, has shown significant promise for multiple seizure types in idiopathic generalized epilepsies, including absence seizures (22).…”
mentioning
confidence: 99%
“…Parker et al () suggested discriminative dysmorphic features, and seizure and behavioral types in SYNGAP1 ‐mutated individuals. Recent report also showed that myopathic facial features became more significant overtime (Prchalova et al ). Table shows the phenotypic comparison between previously identified SYNGAP1 variants and our present patient, who contributes to an expansion of the disease phenotype.…”
Section: Discussionmentioning
confidence: 95%